"Before I am biologically a male, I am me": Exploring gender identity of South Korean male exotic polers. (November 2021) - Kim, Yunjung; Kwon, Sun Yong
The field of sports has traditionally been a domain that practices and reinforces masculinity. However, in contemporary literature, observations and experiences of males in sports have expanded their ideas on masculinity as well as gender identity. Furthermore, there is an increase in males participating in non-orthodox masculine physical activities, most of which are known as "gender appropriate" for females such as cheerleading, dance, gymnastics, etc. Recently, pole dance – a stigmatized female-oriented activity – has become a newly introduced activity in the sports scene and one in which males are gradually engaging in worldwide. In the case of Korea, the phenomenon of men taking part in female-concentrated activities is not common; however, there are a rising number of male pole dancers visible through national competitions and media sources. Therefore, this study explores the experiences of Korean male exotic pole dance practitioners to understand how they define gender identity whilst participating in a highly female-oriented activity. It was found that research participants articulated beyond their biological sex and practice not to conform to social gender roles, and rather emphasized their manifested identity of individual self. Despite Korea's cultural and traditional aspects of gender norms, this study establishes a broader segment of gender ideas and expands the understanding of various identities spoken among male polers.